Malignant Hyperthermia in Bariatric Surgery: A Case Study With Clinical, Pathophysiological, Biochemical and Biophysical Correlations - Oliveira, Pierri E. A.; Salvador, Guilherme H. M. [UNESP]; Marchi-Salvador, Daniela P. (Elmer Press, 2020)
Malignant hyperthermia (MH) is an acute pharmacogenetic disorder, which while uncommon is potentially fatal. MH is a calcium channelopathy of skeletal muscle in which a constant increase of intracytoplasmic Ca2+ concentration occurs causing a change in cellular metabolism. A hypermetabolic state develops when susceptible patients are exposed to halogenated volatile inhalational anesthetic agents and depolarizing muscle relaxants and/or extreme physical activity in hot environments. MH presents variable clinical expression. During an episode of MH, the patient may present clinical signs and laboratory findings including masseter muscle spasm, tachycardia, rise in endtidal CO2 (EtCO2), tachypnea, hyperthermia, cyanosis, metabolic acidosis, rhabdomyolysis, hyperkalemia, myoglobinuria, hyperlactacidemia, and acute renal failure. The aim of this case report is to describe an episode of MH associated with the use of halogenated anesthetic during bariatric surgery. A 29-year-old Brazilian man was admitted to the hospital to undergo a bariatric surgery. The patient’s relevant medical history included morbid obesity grade III, allergy to sulfa-based drugs and severe obstructive sleep apnea. Preoperative evaluations with cardiopulmonary exercise testing, echocardiogram and electrocardiogram showed no anatomical and functional changes of the patient’s heart. Surgical procedures lasted for 4 h, without complications, but the evolution of the patient’s condition indicated oliguria and acute breathing insufficiency. Five hours after the patient was placed under mechanical ventilation in the intensive care unit, he started to present clinical signs of hypermetabolic state, with tremors, excessive sweating, and rapid body temperature increases. In the postoperative period, the patient had hyperglycemia, hypocalcemia, hypernatremia, hyperkalemia, changes in creatine phosphokinase (CPK), aspartate transaminase (AST), alanine aminotransferase ALT), urea and creatine concentrations, and metabolic and respiratory acidosis. Urinalysis showed traces of proteinuria, presence of ketones, leukocytes, red blood cells, and urobilinogen. In our case report, MH crisis was diagnosed late; the dantrolene was not administrated because it was not available and the patient died. This detailed case report of MH episode triggered by isoflurane anesthetic during bariatric surgery allowed us to describe the severity and lethality of this hypermetabolic syndrome. Dantrolene should be mandatory in all operating rooms. Knowledge of the symptoms, an early diagnosis and an adequate treatment can prevent the death of patients in MH crisis
Keywords: Caffeine-halothane contracture test; Dantrolene sodium; Halogenated anesthetic; High CPK concentration; Hypermetabolic state; Metabolic acidosis; Pharmacogenetic disorder; Respiratory acidosis